PEMBATALAN SERTIPIKAT HAK MILIK YANG DITINGKATKAN DARI HAK GUNA BANGUNAN (CONTOH KASUS: PUTUSAN PENGADILAN TATA USAHA NEGARA SERANG NOMOR 58/G/2019/PTUN-SRG) - Adi Dian Permana; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
Land rights are marked by the issuance of a certificate of land rights. This certificate functions as acertificate of title, issued for the benefit of the right holder concerned, in accordance with the physicaldata contained in the measuring document, as long as the physical data and juridical data are inaccordance with the data contained in the letter of measurement and the land book of the titleconcerned. So in this case it is clear that the certificate is a strong means of proof provided by the stateto guarantee legal certainty and certainty of rights, as long as no other party can prove otherwiseregarding the status of ownership. In this case, the certificate can increase the increase to OwnershipRights, but increasing the Ownership Rights does not rule out the possibility of a problem arising. Onecase that occurred was the previous incident that the certificate had been upgraded from Hak Gunawhich occurred at Ruko Permata Cimone, Tangerang City. The beginning of the problem after theletter was issued regarding the mandatory certificate of Ownership which requires the cancellation ofthe certificate of building rights in the name of PT. Purna Bhakti Jaya and its derivatives, namely 22certificates of property rights and 11 certificates of building rights that have been extended. Theowners objected because at the beginning of the issuance of the decree there was no informationregarding the object being submitted.